Cardiovascular-kidney-metabolic Syndrome: a current and urgent concept - Andrea Pio de Abreu; Luciano Ferreira Drager; Madson Queiroz Almeida; Luiz Aparecido Bortolotto; Heno Ferreira Lopes (Brazilian Journal of Nephrology)
Abstract The concept of cardiovascular-kidney-metabolic health is based on the idea of a multifaceted interaction among several cardiovascular, renal, and metabolic factors. Alterations in this complex interaction have a significant impact on morbidity and mortality. The ramifications of poor cardiovascular-kidney-metabolic health are far-reaching, with a notable clinical impact. A considerable proportion of the population is affected by precarious cardiovascular, renal, and metabolic health, and individuals with adverse social determinants of health endure an even greater burden. To this end, it is essential to develop an approach that incorporates metabolic staging and prioritizes lifelong prevention. Equally imperative is integrating the social determinants of health into care models for Cardiovascular-kidney-metabolic syndrome, facilitating patient-centered interdisciplinary care. The American Heart Association (AHA) provides guidelines on the definition, staging, paradigms, and holistic approaches to the management of patients with this syndrome. Furthermore, it offers a comprehensive framework for effectively and equitably improving the cardiovascular, kidney, and metabolic health of the population.